Evaluasi Kinerja Operasional Kereta Komuter Surabaya - Bangil - theresia mca; Nafilah El Hafizah; Kurnia Hadi Putra; Flora Mustikaning Ratu (Institut Teknologi Adhi Tama Surabaya, 2022)
KAI DAOP VIII Ltd operates the commuter train for Surabaya-Bangil route to overcome the needs of people that use train to work. This train is expected to reduce the congestion in Surabaya since there are also citizen outside the city that use it for work. Thus, the performance of train operation must be evaluated such as; travel, stopping, and delay time, convenience of sitting and standing sites, and loading factor. Field survey data were collected and processed by hypothetical test 1- Sample t test. The travel time for Surabaya-Bangil was changed from 66 to 63 minutes based on the schedule while the viceversa route changed from 66 to 55 minutes. The stopping time for Surabaya-Bangil was changed from 43 to 47 minutes based on the schedule while the viceversa route changed from 43 to 50 minutes. The delay time for Surabaya-Bangil had 6 minutes and departure 4 minutes, while for Bangil-Surabaya had the arrival 7 minutes and departure 9 minutes. Those results were under the process of acceptance after the hypothetical test 1-Sample t test is done. The convenience of seat gained 0.3 m2/space in the normal condition and 0.167-0.169 m2/space during COVID-19. Meanwhile, the convenience of standing site obtained 0.25-0.29 m2/space. The loading factor got 36% for Surabaya-Bangil and 29% for Bangil-Surabaya. These results categorized as ineligible for loading factor 70% since this survey was conducted during COVID-19 pandemic.